Analisis Faktor-Faktor Yang Mem Engaruhi Produksi Ledre Pisang Di UD. Dua Putri Dewi, Kota Malang - Charles Labis Welafubun (Fakultas Pertanian, 2022)
The purpose of this study was to find out what factors influenced the production of banana ledre and what were the most dominant factors affecting ledre production at UD. Dua Putri Dewi, Malang City. Independent variables, namely raw material costs, outpouring of labor, total wages and the dependent variable is the amount of ledre banana production. The analysis used in this study uses multiple regression analysis because to determine the effect of each variable production factor. The research variables are raw material costs, labor outlays, and total wages. To find out the effect of each factor of production variables, F test and t test (0,05) were conducted and to find out which dominant production factors were influential, a coefficient regression test was carried out. The results of analysis F test calculated = 6.896 > Ft abel = 2.87 or significantly Fhit ung = 0.001 < 0.05, meaning H0 is rejected and H1 is accepted. This shows together there is a significant influence of production factors on the amount of ledre banana production in UD. Dua Putri Dewi, Malang City. The results of the t-test analysis of the factors of production of raw material costs thit ung = 2.925 > tt abel = 0.68223, outpouring of labor thit ung = 3.142 > tt abel = 0.68223, and the number of wages thit ung = 0.161 > tt abel = 0.68223. The factors of production of raw material costs and outpouring of labor have a significant effect on ledre production at a 95% confidence level. The factor of production of wage amount does not have a significant effect on the amount of ledre production at the 95% confidence level because of the sig value. production factor greater than 0.05.